Analisis Hubungan Literasi Keuangan Investor, Pengetahuan Investor, Risk Tolerance Investor Dan Regret Aversion Bias Investor Dengan Keputusan Investasi - Suciwati, Desak Putu; Marwa, Shaskia Roja; Susanti , Jeni (Jurnal Bisnis dan Kewirausahaan, 2024)
Data of Otoritas Jasa Keuangan (OJK) result that the number of Single Investor Identification (SID) in Indonesia has increased from 2019 to May 2022. Most of these SID investors come from millennials who were born from 1980 to 2000. Investors in Bali SID also experienced an increase, especially in Denpasar City and Badung Regency. The aim of the research is to analyze the relationship between investor of financial literacy, investor knowledge, risk tolerance and regret aversion bias with stock investment decisions in Bali. The sampling technique uses the Slovin formula to obtain a minimum sample size. The data source was obtained from primary data by distributing a 5 Likert scale questionnaire to respondents via Google Form to BNI Securities and Mandiri Securities. Based on the research sample criteria, 129 research samples were obtained. Partial Least Square (PLS) - Structural Equation Modeling (SEM) is used for data analysis. The results are 1) investor financial literacy is significantly positively related to investment decisions, which means hypothesis 1 is accepted, 2) investor knowledge is significantly positively related to investment decisions, which means hypothesis 2 is accepted, 3) investor risk tolerance is significantly positively related to  investment decisions so that Hypothesis 3 is accepted, 4) investor regret aversion bias is significantly positively related to investment decisions, which means hypothesis 4 is accepted.